BIODURIPAVE : INNOVATION OF DURIAN SHELL BIO-OIL IN BIO-ASPHALT PRODUCTION TO REDUCE FOSSIL ENERGY DEPENDENCE - Ilma Zahra; Nabila Salsabila; Sabyla Laila Putri (Yayasan Banu Haji Samsudin, 2025)
Amid the challenges of fossil energy dependence and the environmental impact of the road construction industry, bio-asphalt innovation emerges as a sustainable solution. This study introduces BIODURIPAVE, a bio-oil derived from durian peel waste (Durio zibethinus), as a partial substitute for bitumen in Hot Mix Asphalt (HMA). The bio-oil is extracted through fast pyrolysis at temperatures of 300–500°C, yielding a calorific value of 24.674 MJ/kg with contents of cellulose, hemicellulose, and lignin. The optimal proportion of bio-oil is 5–8% in Pen 60/70 bitumen or Asbuton B 50/30. The results show a reduction in CO₂ emissions by up to 20–30% based on Life Cycle Assessment (LCA), improved oxidation resistance, and enhanced mechanical stability (penetration 60–70, softening point >50°C, Marshall stability >1000 kg). SWOT analysis identifies strengths in local raw materials, opportunities in the circular economy, as well as challenges related to pyrolysis technology and incomplete regulatory frameworks. Implementation is planned in four phases: R&D (2025), pilot (2026), scalability (2027), and national standardization (2028), with potential cost savings of 12–15% per kilometer of road and the creation of 10–15 rural jobs per 5-ton daily production unit. This innovation aligns with the Sustainable Development Goals (SDGs) 7, 9, and 13.